Feasibility and Performance Evaluation of Microprocessor and Fuzzy Logic-Based Overcurrent Relay in Electrical Protection Systems - Parada D.P, Bima Romadhon; Megawati, Citra Dewi; Nurcahyo, Eko; Hidayat, Taufik; Setiawan, Rachmadi; Latif, Kurniadin Abd (Universitas Bumigora, 2024)
This research focuses on the development and testing of a microprocessor-based Overcurrent Relay (OCR) with the implementation of fuzzy logic control for adaptive setting of TMS values. OCR is a crucial component in the electricity protection system which aims to detect and respond to disturbances due to excessive current, preventing damage to electrical equipment. The aim of this research is to test the feasibility and performance of microprocessor-based OCR with fuzzy logic control in setting TMS values, and compare it with the international standard IEC 60255. The method used in this research is the implementation of the Sugeno type fuzzy logic algorithm on the Atmega 328P microcontroller. This algorithm is used to control the TMS value based on the rotating frequency of the detected overcurrent. The results of this research are a characterization of the OCR response to variations in streaming current and different PS settings. The lowest TOp deviation was observed at higher PS settings, with the best performance in the IDMT OCR type. The use of fuzzy logic control is able to increase the OCR response to overcurrent disturbances, although under normal conditions it sometimes results in a longer TOp. The conclusion of this research is that microprocessor-based OCR with fuzzy logic control can provide protection performance that is adaptive and responsive to dynamic operational environmental conditions. This implementation has the potential to increase the efficiency and leakage of the electricity protection system